The method for setting the reliability of financial analysis information - Mackevičius, Jonas; Valkauskas, Romualdas (Information & Media, 2017)
The reliability of financial analysis information is very important for internal and external consumer’s information. Based on the data, this information can be possibly used to determine the company’s chances and perspectives in a competitive market, to properly assess the company's financial condition and the results of its activity. Reliable financial analysis information particularly supplements consumer’s information which is required to make the right decisions and to assess their validity. The function of the reliability of financial analysis information is the accuracy of analytical calculation. Conceptuality, reliability, validity, arrangement, relevance are all dimensions and criteria of analytical calculations that ensure compliance and determine the accuracy of such calculations. This article deals with the value of reliability to financial analysis information. Studied are certain factors which reduce or raise the reliability of financial analysis information. Analytical calculation criteria that ensure the reliability of such calculations are discussed and presented within the article. It is proved that it is rational to apply the hypothetical deductive paradigm to the procedure of financial analysis, and that all financial analysis stages get a credibility problem in their reliability values. The paper presents the solutions to this problem. Therein presented are the methods for producing reliable financial analysis information, in the basis of which lay ten principles of reliability in financial analysis information: sequence, comparison, continuity, variety, accuracy, cost-profit, value, particularity, compatibility and validity.
Keywords: financial analysis; reliability information; the principles; the system